Strategic choice of measures: A Swedish method for deciding on infrastructure investments - Håkonsson, Maria; Abrahamsson, Ulrika (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
Since 2013 the study of strategic choice of measures has been a part of the process for the strategic and economic planning of the transport system in Sweden. The main objective in implementing a new planning process for infrastructure was to ensure safe and cost-efficient solutions which contribute to sustainable development and the fulfilment of the Swedish transport policy. The method for strategic choice of measures is focused on facilitating collaboration between the actors that have a responsibility in planning the transport system as well as enabling involvement of the general public and other actors. The methodology is divided into four phases. Initiate - Making the decision of starting a study, involving the closest concerned actors and deciding on the main aim of the study as well as the cost and time frame. Understand the situation - Defining the problems needs and deficiencies, setting a scope for the study, describing the current situation and the ‘zero option’ and agreeing on which goals the measures should reach. Test possible solutions - Identify possible measures with the help of the ‘four-step principle’ and within all modes of transport and assess the measures to see if they contribute to the goal of the study, is economically sound, does not lead to any negative consequences etc. Form a direction and recommend measures - Recommend measures or a combination of measures and hopefully reach an agreement between the actors. There are some adjustments to be made to the method, but there seems to be a consensus that the method for strategic choice of measures has led to a better understanding of the different actors’ points of views - both the problems and needs within the transport system but also the issues and limitations within their respective organisations. This is something that could benefit the Danish authorities, especially since they have separate authorities for road and railway.